2006
DOI: 10.1099/vir.0.81086-0
|View full text |Cite
|
Sign up to set email alerts
|

VP1 sequences of German porcine parvovirus isolates define two genetic lineages

Abstract: In order to evaluate the genetic variability of Porcine parvovirus (PPV), the complete capsid protein sequences (VP1/VP2) from seven recent field isolates from Germany, one isolate from the UK and one German vaccine strain were sequenced and analysed, along with two American (NADL-2 and Kresse), three Asian and 22 Brazilian partial PPV sequences retrieved from GenBank. The analysis revealed a high degree of diversity: 1?2-2?6 % at the nucleotide level and 1?2-6?8 % at the amino acid level. Phylogenetic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
57
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 15 publications
3
57
0
5
Order By: Relevance
“…Between the genotypes, an overall identity of about 95 % at the amino acid level (VP1) is observed. Amino acid residues 381, 596 and 586 are consistently different between the genotypes (Zimmermann et al, 2006); however, it has not yet been shown that these amino acids determine the Cross-protection against a heterologous PPV genotype antigenic differences (Zeeuw et al, 2007). The viruses that are used in the two vaccines examined in this study are both genotype 1 viruses and differ in the VP1 gene by only 2 %.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Between the genotypes, an overall identity of about 95 % at the amino acid level (VP1) is observed. Amino acid residues 381, 596 and 586 are consistently different between the genotypes (Zimmermann et al, 2006); however, it has not yet been shown that these amino acids determine the Cross-protection against a heterologous PPV genotype antigenic differences (Zeeuw et al, 2007). The viruses that are used in the two vaccines examined in this study are both genotype 1 viruses and differ in the VP1 gene by only 2 %.…”
mentioning
confidence: 72%
“…Fetuses infected before day 70 of gestation usually die, whereas fetuses infected at a later time point develop antibodies against PPV, eliminate the virus and survive the infection (Nielsen et al, 1991). Zimmermann et al (2006) showed that PPV is more diverse than thought previously and that some recent German field isolates differ genetically from the reference and vaccine strains. By phylogenetic analyses based on VP1 sequences, two genotypes could be defined.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…If the fetuses are infected after day 70 of gestation, they usually develop antibodies against PPV and eliminate the virus (Zeeuw et al, 2007;Truyen & Streck, 2012). In recent years, studies have shown that PPV is much more diverse than previously thought (Zimmermann et al 2006;Streck et al, 2011). Several PPV strains of different virulence are known.…”
mentioning
confidence: 99%
“…Based on phylogenetic analyses of the VP1/VP2 protein genes, PPV can be defined into at least seven clusters (Zimmermann et al, 2006;Streck et al, 2011Streck et al, , 2013a. Recently, a population dynamic analysis showed that, despite the high evolutionary rate, only a few PPV strains (similar to strain 27a) have been predominant in Europe in recent years (Streck et al, 2013b).…”
mentioning
confidence: 99%